Activity of ROS-induced processes in the combined preconditioning with amtizol before and after cerebral ischemia in rats - Olga S. Levchenkova; Vasiliy E. Novikov; Viktoriya V. Vorobyova; Konstantin N. Kulagin (Belgorod National Research University, 2021)
Introduction: The dose-dependent effect of reactive oxygen species (ROS) in tissues in preconditioning (PreC) and oxidative stress, as well as NO-synthase participation in mitochondrial ROS production determined the study aim - to assess the impact of the neuroprotective method of combined preconditioning (CPreC) on free radical reactions (FRRs) in brain in normoxia and in cerebral ischemia, including in NO-synthase blockade. Materials and methods: The intensity of FRR by iron-induced chemiluminescence (CL), the content of lipid peroxidation products and antioxidant enzyme activity were investigated 1 hr (early period) and 48 hrs (delayed period) after CPreC (amtizol and hypobaric hypoxia) in Wistar rat brain. Some animal groups were operated (common carotid artery bilateral ligation) 1 hr and 48 hrs after CPreC, as well as with preliminary introduction of L-NAME and aminoguanidine. Results and discussion: In normoxia, CPreC led to increase the CL maximum level (Fmax) in the delayed PreC period. The amount of thiobarbituric acid reactive products (TBA-RP), activity of superoxide dismutase (SOD) and catalase in mitochondrial fraction of rat brain did not change in comparison with the intact control in both PreC periods. In cerebral ischemia, oxidative stress was observed. The CPreC use before ischemia caused a decrease in CL parameters and TBA-RP in brain, the maintenance of SOD and high catalase activity. NO-synthase inhibitors partially abolished the antioxidant effect of CPreC in ischemia. Conclusion: CPreC had no influence on FRRs in brain tissue in normoxia, but prevented their excessive activation after ischemia, especially in the delayed period. NO-synthase was involved in the CPreC neuroprotection.